Optimal Magnetic Resonance Perfusion Thresholds Identifying Ischemic Penumbra and Infarct Core: A Chinese Population‐based Study. (5th December 2014) - Zhang, Sheng; Tang, Huan; Yu, Yan‐Nan; Yan, Shen‐Qiang; Parsons, Mark W.; Lou, Min
Summary Aims To validate whether the optimal magnetic resonance perfusion (MRP) thresholds for ischemic penumbra and infarct core, between voxel and volume‐based analysis, are varied greatly among Chinese acute ischemic stroke patients. Materials and methods Acute ischemic stroke patients receiving intravenous thrombolysis within 6 h of onset that obtained acute and 24‐h MRP were reviewed. Patients with either no reperfusion (<30% reperfusion at 24 h) or successful reperfusion (>70% reperfusion at 24 h) were enrolled to investigate the ischemic penumbra and infarct core, respectively. The final infarct was assessed on 24‐h diffusion‐weighted imaging (DWI), which was retrospectively matched to the baseline perfusion‐weighted imaging (PWI) images by volume or voxel‐based analysis. The optimal thresholds that determined by each approach were compared. Results From June 2009 to Jan 2014, of 50 patients enrolled, 19 patients achieved no reperfusion, and 20 patients reperfused at 24 h. In patients with no reperfusion, Tmax > 6 seconds was proved of the best agreement with the final infarct in both volumetric analysis (ratio: 1.05, 95% limits of agreement:−0.23 to 2.33, P < 0.001) and voxel‐by‐voxel analysis (sensitivity: 72.3%, specificity: 74.3%). In patients with reperfusion, rMTT>225% (ratio:2.4, 95% limits of agreement: −6.5 to 11.4, P < 0.001) was found of the best volumetric agreement with the final infarct, while Tmax > 5.6 seconds (sensitivity: 76.8%, specificity: 70.3%) performed most accurately in voxel‐based analysis. Conclusion Among Chinese acute stroke patients, volume of Tmax >6 seconds may precisely target ischemic penumbra tissue as good as voxel‐based analysis performed, albeit no concordant MRP parameter is found to accurately predict infarct core because reperfusion occurred within 24 h after thrombolysis fails to restrain the infarct growth.